Preparation methods, biological activities, and potential applications of marine algae oligosaccharides: a review - Li-Xin Zheng; Yang Liu; Shijie Tang; Wancong Zhang; Kit-Leong Cheong (Food Science and Human Wellness)
Marine algae are valuable sources of health-promoting molecules that have been consumed by Asians for decades. Among aquatic flora, marine algae stand out in terms of high content of marine algae polysaccharides (MAP) such as carrageenan, alginate, fucoidan, laminaran, agarose, rhamnan, and ulvan. When hydrolyzed, MAP generate marine algae oligosaccharides (MAO), which have attracted interest in recent years due to their superior solubility compared with MAP. Besides, MAO have been demonstrated numerous biological activities including antioxidant, antidiabetic, anti-inflammatory, antimicrobial, and prebiotic activities. Thus, this review summarizes the main chemical classes of MAO, their sources, and the main processes used for their production (i.e., physical, chemical, and biological methods), coupled with a discussion of the advantages and disadvantages of these methods. Highlights of the biological activities of MAO and their potential applications in food, nutraceutical, and pharmaceuticals would also be discussed and summarized.